VITAL PULPTHERAPY: MODERNTRENDS - Xudayberganova.M.X, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: To analyze modern trends and the evolution of materials used in vital pulp therapy. A review of clinical studies and meta-analyses conducted between 1960 and 2016 with a 12-month follow-up period was performed. The review highlights the shift from traditional materials like formocresol to bioactive materials such as Mineral Trioxide  Aggregate  (MTA)  and  Biodentine.  MTA  demonstrated  superior biocompatibility and reparative properties compared to calcium hydroxide. Vital pulp therapy  remains  a  biologically  oriented  and  reliable  approach,  with  modern biomaterials significantly improving clinical outcomes. Keywords: Vital pulp therapy, pulpotomy,  mineral  trioxide  aggregate  (MTA),  formocresol,  pulpitis,  bioceramics, apexogenesis, primary teeth, dentistry, bioactive materials.